Boost Selectivity of HCOO− Using Anchored Bi Single Atoms towards CO2 Reduction. Issue 23 (3rd September 2020) - Yang, Xupeng; Chen, Yuliang; Qin, Lang; Wu, Xiaonan; Wu, Yuting; Yan, Tao; Geng, Zhigang; Zeng, Jie
Abstract: Single atoms have been widely applied as efficient catalysts in various catalytic systems due to its high selectivity for certain products, which is induced by a uniform coordinate environment of active sites. Herein, it is demonstrated that Bi single atoms anchored on carbon black (Bi SAs/C) can serve as an efficient catalyst for CO2 electroreduction into formate (HCOO − ). During CO2 electroreduction, Bi SAs/C achieved a faradaic efficiency for HCOO − of 83.6 % at−1.1 Vversus reversible hydrogen electrode (V vs. RHE). Notably, the selectivity for HCOO − of Bi SAs/C was always higher than 95 % at all applied potentials. In addition, at−1.2 Vvs.RHE, the current density for HCOO − formation in thepresence of Bi SAs/C reached−12.0 mA cm −2, which was 3.4 times as high as that (−3.5 mA cm −2 ) of BiO x clusters on carbon black (BiO x /C). Mechanistic studies revealed that Bi SAs/C facilitated the faradaic process and accelerated reaction kinetics in comparison with BiO x /C. Abstract : Highly efficient single Bi sites towards carbon dioxide electroreduction : Atomically dispersed Bi atoms on carbon black served as highly selective active sites towards carbon dioxide electroreduction into formate. The direct bonding of Bi with oxygen species on carbon black stabilized the atomic dispersion of Bi, facilitating charge transfer between substrate and active Bi sites and promoting reaction kinetics, resulting in enhanced selectivity for HCOO − of higher than 95 % with high catalytic stability for more than 10 h for Bi single‐atom catalysts.